Gene Therapy for Glioblastoma Multiforme - Smit Shah; Joshua Green; Shantelle A. Graff; Qi Li; John D. Heiss (Viruses)
Glioblastoma multiforme (GBM) is a devastating, aggressive primary brain tumor with poor patient outcomes and a five-year survival of less than 10%. Significant limitations to effective GBM treatment include poor drug delivery across the blood–brain barrier, drug resistance, and complex genetic tumor alterations. Gene therapy uses a mechanism different from other GBM therapies to reduce tumor growth and enhance antitumor immunity. This review article will provide an update on various viral and nonviral vectors, their DNA and RNA cargoes, and how they genetically modify tumor cells and evoke therapeutic responses to GBM. The article explores the oncolytic and immunogenic effects of gene therapy agents. It reviews promising DNA transgenes, RNA inhibitors, and vectors for anti-GBM therapy. The possible benefits of combining gene therapy with standard GBM treatments will also be covered.